EFEKTIVITAS PROGRAM KELUARGA BERENCANA METODE KONTRASEPSI JANGKA PANJANG DI KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - jurnalmap map; Misni Hayati S; Hadi Susanto; Sri Mulyani (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
This study aims to describe the Effectiveness of the Long Term Contraception Method Family Planning Program in Indragiri Hilir Regency. This type of research is descriptive with qualitative methods. Research data obtained from interviews, observations and documentation. Data analysis uses interactive data analysis from Miles and Huberman. Based on the results of the study obtained information that the Family Planning Program in Indragiri Hilir Regency is quite effective in suppressing the population growth rate. Judging from the several indicators used to measure Program Effectiveness, namely: Seen from the Program Objectives. Program Objectives in this case, the Fertile Age Couple. The effectiveness of the Targets as seen from the number of EFAs as active KB participants over the past 4 years has continued to increase, but those using the Long-Term Contraception Method have decreased each year. Keywords: family planning, long-term contraception method